EMOJIS AFFECT THE MEANING OF SARCASM SENTENCES ON SOCIAL MEDIA TWITTER: EVIDENCE FROM INDONESIA MILLENNIAL GENERATIONS - Ratna Sari Dewi (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This study discusses the semiotic analysis related to the sarcasm emoji used by users on social media Twitter. This study aims to describe the types of emojis sarcasm and how emojis affects users on Twitter. This research used a qualitative descriptive research. The data source are taken from user comments on Twitter from March to May 2023 on the @indomielovers account. The results showed that there were 3 types of emojis sarcasm found, namely: no emojis, positive emojis, and negative emojis in comments on the Twitter account @indomielovers. There are 100 comments consisting of 40 types of no emojis, 30 types of positive emojis and 30 types of negative emoji. Then, the researcher found the factors of using sarcasm emoji, namely thoughts, expressions, and opinions. and the affects of using sarcasm emojis are that they can lead to misunderstandings or misinterpretations and making sentences more emotional that offend someone, then cause confusion and conflict. Also, most of the users use sarcasm emoji based on the post they want to comment on that post.